2021
DOI: 10.1177/1368430220967978
|View full text |Cite
|
Sign up to set email alerts
|

Why we can’t talk openly about race: The impact of race and partisanship on respondents’ perceptions of intergroup conversations

Abstract: Conversations about race-specific issues with interracial conversation partners can be important to combat prejudice and foster mutual understanding. Using a national U.S. sample of 201 Black Democrats, 199 Black Republicans, 200 White Democrats, and 200 White Republicans, this study examined the role that race and partisanship play in individuals’ desire to have political discussions about race-specific topics with racial outgroups. Findings indicate that Blacks in general expected more negative outcomes of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…For instance, salient multiculturalism heightens the perceptions of both realistic and symbolic threat among dominant group members high in RWA (Kauff et al, 2013), as well as perceptions of realistic threat among dominant group members high in SDO (Gutiérrez & Saint Clair, 2018). Regarding relational threat, one recent study found that White conservatives in the United States were more likely than Black conservatives, White liberals, and Black liberals to want to avoid interracial discussions about topics such as police treatment of Black Americans and Black NFL players kneeling during the U.S. national anthem (Appiah et al, 2022). Although this study did not directly assess threat, talking about controversial racial issues—which often involves acknowledging differences (i.e., a multicultural mind-set)—could have been perceived as compromising the quality of the interaction (see Sasaki & Vorauer, 2013; Vorauer & Sasaki, 2011).…”
Section: Introducing the Multiculturalism And Colorblindness As Threa...mentioning
confidence: 99%
“…For instance, salient multiculturalism heightens the perceptions of both realistic and symbolic threat among dominant group members high in RWA (Kauff et al, 2013), as well as perceptions of realistic threat among dominant group members high in SDO (Gutiérrez & Saint Clair, 2018). Regarding relational threat, one recent study found that White conservatives in the United States were more likely than Black conservatives, White liberals, and Black liberals to want to avoid interracial discussions about topics such as police treatment of Black Americans and Black NFL players kneeling during the U.S. national anthem (Appiah et al, 2022). Although this study did not directly assess threat, talking about controversial racial issues—which often involves acknowledging differences (i.e., a multicultural mind-set)—could have been perceived as compromising the quality of the interaction (see Sasaki & Vorauer, 2013; Vorauer & Sasaki, 2011).…”
Section: Introducing the Multiculturalism And Colorblindness As Threa...mentioning
confidence: 99%
“…Recent research indicates that belonging to multiple different groups (i.e., intersectionality ) may have nuanced effects on group processes (Nicolas et al, 2017). For instance, race deferentially impacted Democrats’ and Republicans’ willingness to engage in race-related political discussions (Appiah et al, 2021). Future research should thus investigate whether intersectionality qualifies as a moderator of the partisan ISE.…”
Section: Discussionmentioning
confidence: 99%
“…Consider, first, that members of disadvantaged groups have a stronger desire than members of advantaged groups to have discussions about group-based power (Saguy et al, 2008), Black individuals find interracial discussions of race-relevant topics relatively less stressful than do White individuals (Trawalter & Richeson, 2008) and, in general, dialogues about intergroup issues are important for progress toward greater social justice (see, e.g., Trawalter & Richeson, 2008). Yet, at the same time, recent work suggests that relative to White individuals, Black individuals expect more negative outcomes—some involving feelings of constraint (i.e., “one or both of us would feel forced to act as a ‘spokesperson’ for our race”)—to arise from intergroup discussions of issues such as White individuals displaying the Confederate flag (Appiah et al, 2021). Although these various findings are not necessarily in conflict with one another, they nonetheless suggest the potential for a more fine-grained analysis to provide greater insight into the power dynamics of discussions of intergroup issues.…”
Section: Experience Focusing and Power Dynamics In Intergroup Interac...mentioning
confidence: 99%